SADD AL-DZARI’AH:KORELASI DAN PENERAPANNYA DALAM HUKUM EKONOMI SYARIAH - rukhul amin (Universitas Muhammadiyah Surabaya, 2020)
This paper describes the importance of sad al-dzari'ah in determining Islamic law, especially in relation to the business-economy world which tends to be dynamic. Sadd al-dzari'ah is a legal instrument in Islam that is good if it is applied properly, in accordance with the rules of syara '. It can be a tool that can be used to create the benefit of the people and prevent it from being damaged. One example that can be seen in seeing the importance of sadd al-dzariah in the national legal system is the application of the actio paulina principle, the regulations of which can be found in Articles 1341 and 1061 of the Civil Code and Articles 41 to 47 of the bankruptcy law. However, as it plays a very important role in the search for law, on the one hand sadd al-dzari'ah can also be something negative. This can happen if the use or application is not / not done carefully, especially if it is not based on broad social piety in the community. Keyword: Sadd/Fath al-Dzari’ah, Maqashid al-Syariah, Actio Paulina